A Leash on Life: An Exploratory Study on the Effects of a Shelter-Dog Walking Program for Veterans on Dogs' Stress. (2nd January 2022) - Friedmann, Erika; Krause-Parello, Cheryl A.; Payton, Megan; Blanchard, Kelly; Storm, Asha; Barr, Erik; Gee, Nancy R.
ABSTRACT: Human–animal interaction (HAI) such a dog walking is used as an intervention to decrease stress in individuals with Post-traumatic Stress Disorder (PTSD). However, it is important to know whether PTSD symptoms of a dog walker and the walk itself stress the shelter dogs. This exploratory project evaluated the impact of a shelter-dog walking program for veterans on stress experienced by the dogs. It also examined whether the PTSD status of the veteran influenced the impact of the walk on the dog. Prior to data collection university, IRB/IACUC approvals were obtained. Shelter dogs ( n  = 25) were walked by veterans who were participating in an 8-week walking program. Seventeen of the walks (45%) were by veterans who reported PTSD. Dog stress was assessed with heart rate variability (HRV) measured for 24 h before, during, and for one hour after the veteran's first and last walks. The walks were designed to take 30 min. The study included 38 walks by 25 dogs and their 28 veteran walkers. The dogs were largely male (60%) and mixed breeds (80%). Sizes of dogs were approximately equally distributed between small, medium, and large sizes. Dog stress was not significantly higher during dog walks when compared with similar times of day in the previous day or with the period immediately prior to the walk. Post-walk, dog stress was significantly lower after walks with veterans with PTSD (HRV M  = 11.64, SD  = 0.15, p  = 0.01, d  = 1.09) than for walks with veterans without PTSD (HRV M   =  11.42, SD  = 0.28). This study provided no evidence that being walked by veterans with PTSD was stressful for shelter dogs despite the unfamiliarity of the veteran dog walkers. Future studies with larger sample sizes in multiple shelters should be conducted to extend the current results.